Mental health issue during the COVID-19 pandemic - Dwi Jazimah Wijayati; Eko Priyo Purnomo; Aqil Teguh Fathani (Intelektual Pustaka Media Utama, 2023)
One of the sustainable development goals (SDGs) is point 3: good health and well-being. This study aims to determine how people’s mental health fared during the COVID-19 pandemic. A library review is the most appropriate method to analyze mental health issues during the COVID-19 pandemic for the past three years. This study is based on articles that met international standards and data collected while searching for a database on Scopus. The results of the study on mental health issues during this pandemic were quite bad because of several government policies that changed people’s lifestyles, causing various levels of anxiety in the community so that stress and depression emerged in the community, even though the government decided to break the chain of the spread of COVID-19. Factors that affect mental health during the pandemic, namely significant lifestyle changes that limit the space for people to move, which result in depression, stress, and sleep disturbances that can cause death, become a pressure on the community, which can worsen people’s thinking and result in a decrease in community immunity. Ignorance and fear of the COVID-19 pandemic, with lockdowns and the economic crisis, have increased mental illness leading to suicide.